Az ócsai premontrei templom építéstörténete és díszítési rétegeei - Raffay, Endre (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: ócsa

Az ócsai premontrei prépostság régészeti kutatása - Csoltkó, Emese (Micae mediaevales VII. Fiatal történészek dolgozatai a középkori Magyarországról és Európáról, 2018)
The village of Ócsa is situated to the south of Budapest in Pest County. The first mention of the existence of the Premonstratensian provostry is dated to 1234 in the so-called Catalogue of Ninive, which mentions that Ócsa is the filial of the convent of Jászó ( Jasov, Slovakia). The church with three naves and two towers at its western facade was built in the first half of the 13th century. During the construction works there were some modifications in the original plans, as the church was planned with another vaulting section towards at the west, but that was, along with the vaulting of the naves, never finished. Minor reconstruction works can be dated to the Middle Ages; for example wall-paintings and the Gothic pastoforium. The Premonstratensians left Ócsa before the Ottoman occupation period, but as a parish church, it didn’t lose the function which is attested by the 15th century demolition of the rood-screen. The church was used by the Calvinist congregation since 1560. As part of the preparation for the reconstruction works, there was archaeological research between 1986 and 1992 which was led by Juan Cabello. This included a systematic, full-scale excavation in the church and in the churchyard. In the course of the excavation, the monastery building with the one side and three pit houses from the 12th–13th century was found. The surrounding and inside of the church were used as a cemetery. The first reconstruction work was realized in the second half of the 18th century ( József Teleki’s works between 1774 and 1777). In the 18th century the church was damaged by natural disasters like lightning and fire. Thus another renovation was necessary, led by Ottó Tandor (1897–1900). In 1909 Ottó Sztehlo renewed the damaged northern portal. The elevation of the towers of the church was carried out by Ernő Foerk in 1923. Finally, the recent renovation of the church was conducted by Tibor Gál between 1989 and 1995.
Keywords: ócsa

Az ócsai református (egykor premontrei) templom építéstörténetének vázlata - Csoltkó, Emese (A múltnak kútja: Fiatal középkoros régészek V. konferenciájának tanulmánykötete, 2014)
[Sketches to the Building History of the Calvinist (Former Premonstratensian) Church of Ócsa]
Keywords: ócsa